Next generation smart car park - Goh, Garrick Chun Hou (Nanyang Technological University, 2024)
As Singapore faces the dual challenge of limited land resources and a rising number of vehicles, innovative parking solutions are essential. This project addresses the problems which arise from increased car ownership and the government's push for a car-lite initiative, which aims to repurpose parking spaces for alternative uses. With a reduction in available parking space and a growing vehicle population, an efficient parking system has to be implemented, to make full use of the urban landscape around Singapore. This study proposes the design and implementation of an automated car parking system that maximizes land utilization. By adopting a single, optimized parking layout equipped with automated mechanisms, this system eliminates the need for walkways and ramps, allowing for a greater density of parking spaces within the same footprint. The project will focus on evaluating hardware performance and will utilize simulations to assess the system's efficiency and aid in mitigating the parking challenges faced in a densely populated urban environment.